Design Middleware untuk Koneksi dan Interoperability Aplikasi dan Database di Bank - David Jefri Aruan; Jan Everhard Riwurohi; Bagus T Prabawa (Jurnal ICT: Information Communication & Technology, 2024)
In the digital banking industry, banking activities ranging from opening an account, transfers, deposits, to closing an account no longer have to go directly through a bank office or via an ATM (Automatic Teller Machine) but can be done via a smartphone/electronic device. In fact, the trend of digital transactions is increasing, this is confirmed by ASPI in its statistical report. The communication message formats commonly used in banking today are ISO 8583, JSON and WSDL. Indonesia developed BIFAST for payment system infrastructure. Middleware was developed to help solve the interconnection of several applications and interoperability problems. Middleware is needed to migrate from mainframe applications to client/server applications and also to provide communication between different platforms